2003
DOI: 10.1089/104454703768247792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Power Radiation (Helium/Neon) upon Submandibulary Glands

Abstract: We propose that low-power laser radiation with the doses applied in this study disturbs protein synthesis and secretion of guinea pig submandibulary glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 24 publications
1
8
0
5
Order By: Relevance
“…Furthermore, anti-apoptosis proteins were detected after laser irradiation. The results of this study suggest that high-power output irradiation of cells using the Ga-Al-As diode laser does not cause the kind of severe degenerative change shown by Samar et al and Plavnik et al who used He-Ne laser irradiation [9,10], and it would be associated with apoptosis-inhibiting proteins such as HSP25 and bcl-2.…”
Section: Irradiation Energy Densitymentioning
confidence: 48%
See 4 more Smart Citations
“…Furthermore, anti-apoptosis proteins were detected after laser irradiation. The results of this study suggest that high-power output irradiation of cells using the Ga-Al-As diode laser does not cause the kind of severe degenerative change shown by Samar et al and Plavnik et al who used He-Ne laser irradiation [9,10], and it would be associated with apoptosis-inhibiting proteins such as HSP25 and bcl-2.…”
Section: Irradiation Energy Densitymentioning
confidence: 48%
“…Samar et al and Plavnik et al reported degenerative and necrotic changes using He-Ne laser irradiation [9,10], while Takeda showed frequent mitotic findings in granular duct cells following gallium-arsenide (Ga-As) low-level laser irradiation at 24 h, suggesting a mitogenic effect with low-level laser irradiation [13]. In the present study, we found that the number of Par-C10 cells in the irradiated groups was higher than that in the non-irradiated group.…”
Section: Cell Growthmentioning
confidence: 99%
See 3 more Smart Citations